(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
In the construction of the current Uzbek literary language, terminology is distinguished by its special place and status. There are two worldviews about the role of terminology in language vocabulary. According to the first idea, terminology is recognized as an independent layer of the lexicon of the literary language, according to the second theory, it is separated from the composition of the vocabulary of the literary language, evaluated as a "separate" object and equated to types of speech (dialect, slang, colloquial speech). [1;136]